Equine “Idiopathic” and Infundibular Caries-Related Cheek Teeth Fractures: A Long-Term Study of 486 Fractured Teeth in 300 Horses - Dixon, Padraic Martin; Kennedy, Rebekah; Reardon, Richard J. M. (Frontiers in Veterinary Science, 2021)
Background Limited objective information is available on the prevalence of the different non-traumatic dental fractures, or on their potential associations with age, tooth position, clinical signs and deemed necessity for treatment. Objectives Document patterns of cheek teeth fractures in a referral population. Evaluate associations between fracture patterns and: horse age, Triadan position of affected teeth, clinical signs, and deemed necessity for treatment. Study design Retrospective case review. Methods The clinical records at Edinburgh University Veterinary School (2010-2018) were examined for the presence of non-traumatic equine cheek teeth fractures. Variations in the frequencies of different fracture patterns were compared between horse ages, Triadan tooth positions, clinical signs and deemed necessity for treatment. Results Records of 300 horses with 486 non-traumatic cheek teeth fractures including 77% maxillary and 23% mandibular teeth with a mean of 1.6 (range 1-10) fractured teeth/horse were available. Fracture patterns included maxillary 1st and 2nd pulp horn (“slab”) cheek teeth fractures (n=171); caries-related infundibular fractures (n=88); other maxillary teeth fracture patterns (n=92); mandibular 1st and 2nd pulp horn (“slab”) fractures (n=44); other mandibular fracture patterns (n=62) and complete clinical crown loss (n=29). The median age of affected horses ranged from 11 years with maxillary “slab” fractures to 15 years with infundibular caries related fractures. Triadan 08s-10s were the most commonly (86%) fractured maxillary teeth. The Triadan 08 and 09 positions were the most commonly (64%) fractured mandibular teeth. No clinical signs were noted in horses with 48% of the fractured teeth; oral pain/quidding was recorded with 25.9%, clinical apical infection with 23% and bitting/headshaking problems with 6%. Treatments included extraction of 40% fractured teeth; extraction of small/loose fragments (10%) and odontoplasty. Stable remnants of 60% of fractured teeth were left in horses without clinical signs. Main Limitations Long-term follow up information was not available for all cases. Conclusions There is increasing recognition of equine non-traumatic cheek teeth fractures, with about half not causing clinical signs. Teeth with apical infection; multiple fractures or advanced caries require extraction. Other fractured teeth with subclinical endodontic disease may not need exodontia unless they later cause clinical signs.